2015
DOI: 10.1371/journal.pone.0116743
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Super-Shedder Strains of Escherichia coli O157:H7 Reveals Distinctive Genomic Features and a Strongly Aggregative Adherent Phenotype on Bovine Rectoanal Junction Squamous Epithelial Cells

Abstract: Shiga toxin-producing Escherichia coli O157:H7 (O157) are significant foodborne pathogens and pose a serious threat to public health worldwide. The major reservoirs of O157 are asymptomatic cattle which harbor the organism in the terminal recto-anal junction (RAJ). Some colonized animals, referred to as “super-shedders” (SS), are known to shed O157 in exceptionally large numbers (>104 CFU/g of feces). Recent studies suggest that SS cattle play a major role in the prevalence and transmission of O157, but little… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
79
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(88 citation statements)
references
References 89 publications
7
79
2
Order By: Relevance
“…In addition, all SS-O157 and control O157 strains adhered to HEp-2 cells in a "diffuse and moderate" pattern (Table 1). An initial screening on CRI plates confirmed that the control strains were curli-expressing (C ϩ ) strains as reported in other studies (27), but the SS-O157 strains differed in their levels of curli production, with only strains SS-12 and SS-42 appearing to be C ϩ (34,35). Since neither the RSE cell adherence patterns nor the HEp-2 cell adherence patterns of these O157 strains could be associated with their respective curli phenotype (Table 1), it appeared that, in contrast to previous reports (25)(26)(27)29), the adherence was not dependent on the curli fimbriae.…”
supporting
confidence: 76%
See 4 more Smart Citations
“…In addition, all SS-O157 and control O157 strains adhered to HEp-2 cells in a "diffuse and moderate" pattern (Table 1). An initial screening on CRI plates confirmed that the control strains were curli-expressing (C ϩ ) strains as reported in other studies (27), but the SS-O157 strains differed in their levels of curli production, with only strains SS-12 and SS-42 appearing to be C ϩ (34,35). Since neither the RSE cell adherence patterns nor the HEp-2 cell adherence patterns of these O157 strains could be associated with their respective curli phenotype (Table 1), it appeared that, in contrast to previous reports (25)(26)(27)29), the adherence was not dependent on the curli fimbriae.…”
supporting
confidence: 76%
“…Eight previously characterized O157 isolates obtained from supershedding cattle were used in this study (34,35). These supershed (SS) O157 isolates included SS-7, SS-12, SS-17, SS-27, SS-42, SS-52, SS-67, and SS-77 (Table 1) (34,35).…”
Section: Bacterial Strains (I) O157 Wild-type Isolatesmentioning
confidence: 99%
See 3 more Smart Citations